2018
DOI: 10.1093/ajcn/nqx056
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and categorizing spurious weight data in electronic medical records

Abstract: Spurious weights are common in EMRs. Straightforward algorithms can identify and remove them, and thus enhance the reliability of EMR data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…SITAR (Superimposition by Translation And Rotation) [28] and the 'Outliergram' [29] are visualisation methods that allow individual trajectories to be viewed but are specific to each dataset they are applied to and require subjective judgements to be made, which can be time consuming when applied to large datasets. Algorithms that examine the change between two measurements are simple to apply in comparison with many longitudinal methods but are limited by poor specificity and are not cable of identifying consecutive errors [30]. Daymont and colleagues designed an automated data cleaning technique based on exponentially weighted moving average standard deviation scores combined with a decision-making algorithm to identify implausible growth data.…”
Section: Introductionmentioning
confidence: 99%
“…SITAR (Superimposition by Translation And Rotation) [28] and the 'Outliergram' [29] are visualisation methods that allow individual trajectories to be viewed but are specific to each dataset they are applied to and require subjective judgements to be made, which can be time consuming when applied to large datasets. Algorithms that examine the change between two measurements are simple to apply in comparison with many longitudinal methods but are limited by poor specificity and are not cable of identifying consecutive errors [30]. Daymont and colleagues designed an automated data cleaning technique based on exponentially weighted moving average standard deviation scores combined with a decision-making algorithm to identify implausible growth data.…”
Section: Introductionmentioning
confidence: 99%
“…Approaches include the use of change scores (13, 18) and % change (3), residuals from OLS regression (28, 32), multilevel models (MLM) (23, 35) and non-parametric smoothing routines (9), conditional growth scores (36) and ratios of Euclidean distances between a set of 3 measures (3). Some studies report using manual verification of growth histories (9, 26) (15) (3) (17), which is considered the gold standard approach. Certain methods require more data points which may be a limitation, and some methods perform poorly when the error load (magnitude and frequency of errors) is high (9, 35).…”
Section: Methodsmentioning
confidence: 99%
“…Lawman et al's., 2016 (8) review of approaches to identify height and weight BIVs was used as a starting to identify the different approaches that have been used for error detection. The 12 studies reported in their Table 1 (11-22) were screened along with all subsequent citations of Lawman et al (8) up to Oct 2020 (n=12) (3,9,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The reference lists of these citing papers were also screened to identify methodological papers describing cleaning algorithms or approaches (n=5) (7, [33][34][35][36].…”
Section: Scoping Review Of Approaches For Identifying Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking into the biomedical literature, we were surprised to find quite scarce reporting about clinical data cleansing (Beaulieu-Jones et al 2018;Chen et al 2018;Coiera et al 2016;Ehrenstein et al 2017). It appears to us that not all in the community are aware of the scale of the problems.…”
Section: Usefulness Of Patient Datasets For Biomedical Research: Whatmentioning
confidence: 99%